USULAN PERBAIKAN KESALAHAN PENETAPAN NILAI PABEAN PADA PT SKA MENGGUNAKAN METODE FAILURE MODE EFFECTS ANALYSIS (FMEA) - Salsabila Amanda (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
PT SKA carried out import activities in 2022 totaling 418 import documents and experienced errors when inputting data on the PIB document where the data for determining customs value was 33 errors, exporter data was 5 errors and carrier data was 3 errors with a total error in the PIB document with 41 mistakes in 2022. This study will use the Failure Mode Effects Analysis (FMEA) method, which aims to find out the root causes of errors in determining the customs value at PT SKA and provide suggestions for improvements so that there are no errors in determining the customs value in the PIB document. The stages of the research were carried out to evaluate the Severity, Occurrence and Detection ratings of each error mode, then calculate the Risk Priority Number (RPN), followed by rating the RPN and making suggestions for improvements to overcome the errors. Determination of the error mode and rating evaluation is given through a questionnaire filled out by 4 employees who work in their fields. The results of this research using the FMEA method show the 3 highest RPN results, namely inputting documents at the end of time with an RPN of 371.25, lack of document checking with an RPN value of 268.13 and documents combined with other documents with an RPN value of 195.50. The highest RPN is inputting documents at the end of time with a value of 371.25 which is the highest risk that corrective action must be taken immediately.